1996
DOI: 10.1159/000185002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concept before and after Two Years of Growth Hormone Treatment in Intrauterine Growth-Retarded Children

Abstract: The objective of this study was to assess self-concept in children with short stature after intrauterine growth retardation (IUGR), before and after 2 years of growth hormone (hGH) treatment. We assessed 25 children before treatment, and 40 children after a 2-year treatment period. Seventeen of the 25 children of whom we had pretreatment data, were reassessed after 2 years of hGH treatment. All children had a birth length below the 3rd percentile, and did not show catch-up growth (current height < P3). We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
4
10
1
Order By: Relevance
“…Furthermore, the change of test instrument during the study could also have favored the positive evolution of IQ scores in the untreated group since a higher number had a change of test instrument, which was found to be related to a significant increase in PIQ scores. The absence of a beneficial effect of GH therapy on IQ scores in our study is in contradiction with the data of two other studies, reporting a significant increase in performance IQ scores in short SGA children after 2 and 8 years of GH therapy respectively (10,12). Some caution is, however, needed when comparing our results with these two studies, since they were both uncontrolled and included children of an older age range.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the change of test instrument during the study could also have favored the positive evolution of IQ scores in the untreated group since a higher number had a change of test instrument, which was found to be related to a significant increase in PIQ scores. The absence of a beneficial effect of GH therapy on IQ scores in our study is in contradiction with the data of two other studies, reporting a significant increase in performance IQ scores in short SGA children after 2 and 8 years of GH therapy respectively (10,12). Some caution is, however, needed when comparing our results with these two studies, since they were both uncontrolled and included children of an older age range.…”
Section: Discussioncontrasting
confidence: 99%
“…This percentage might be an underestimation given the use of rather older test instruments in our study, as mean scores on IQ tests increase each decade (known as the Flynn effect). The findings of lower intellectual capacities and recurrent health problems are consistent with those reported in several other publications on the cognitive development of SGA children (3,10,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). It is somewhat surprising that none of these previous studies referred to the need of specialized help in these children, which was noted to be provided in one-third of the patients in the present study, excluding, however, children with severe mental retardation, but including some children with minor dysmorphisms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A 2-yr psychosocial evaluation in the children of our study showed a beneficial effect on behavioral and emotional problems and on the self-concept of the children (43,44). Further psychosocial research will be performed to confirm this improvement.…”
Section: Discussionsupporting
confidence: 54%
“…The influence of these short-term gains on final adult height has not been established, although an improvement in final height prognosis (based on height standard deviation scores for bone age) has been observed in IUGR (Hokken-Koelega 1999, Mehta & Hindmarsh 2002. Although QoL has not been measured in IUGR using specific tests, deficits in IQ, attention and selfconcept (Hokken-Koelega 1999) have been documented, and attention, peer acceptance and self-worth have been shown to be improved by GH therapy ( Van der Reijden et al 1996. QoL has not been examined in most other childhood conditions associated with impaired growth.…”
Section: Other Disordersmentioning
confidence: 99%